Penerapan Model Pembelajaran Inquiry untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran Geografi dengan Materi Pokok Dinamika Kependudukan di Indonesia Kelas XI SMAN 10 Kota Jambi - Ermiwati Ermiwati (Universitas Batanghari Jambi, 2021)
This research aims to determine the effectiveness of student learning outcomes in Geography subjects with the subject of Population Dynamics in Indonesia class XI IPS 1 SMAN 10 Jambi using inquiry learning model. Population and samples in this study were students of class XI IPS 1, amounting to 30 students. The data obtained based on this study Based on the results obtained in the above study between the two cycles it can be obtained data that in cycle 1 the average value of student learning activities in first cycle was 2.6 while the average value in second cycle was obtained. amounted to 3,4. This shows that there is an increase in student learning activities. Based on the results obtained in the above research, between the two cycles, it can be obtained data that in first cycle the average value of teacher activity was 3.4, and the average value insecond cycle was 3.5. This shows that there is an increase in teacher activity. Based on the results obtained in the above research, especially on the subject of Population Dynamics in Indonesia, there are significant results on student learning completeness in first cycle and second cycle was 10%.